Repurchase intention: The effect of e-service quality and customer satisfaction - Yurika Putri Hendika; Muthia Roza Linda (Universitas Negeri Padang, 2022)
The study purpose was to examine the quality of e-service impact on intention of repurchase with the satisfaction of customer as a variable of mediating for Shopee users in Pariaman. Primary data from surveys that were distributed online with the aid of Google Forms were used in this study. People who have used and purchased from the Shopee marketplace are required to complete the survey. 110 respondents in total. The analysis tool makes use of SmartPLS 3.3.9. The results of the analysis show that the influence of e-service quality has an impact was significant on the intention of repurchase as evidenced by the P-Value score of 0.000 < ( = 0.05) . The influence of quality of e-service has an impact was significantly satisfaction customer as evidenced by the P-Value score of 0.000 < ( = 0.05 ), then the influence on satisfaction of customer has an impact was significant on repurchase intention with a P-Value of 0.000 < ( = 0.05 ), then the Customer Satisfaction variable has a significant impact as a variable of mediating between quality of e-service and intention of repurchase through a P-Value score of 0.000 < ( = 0.05).